Switched magnetic field motor/generator - Chu, Andrew Jian Tek. (2011)
It is commonly accepted that the earth’s fossil energy resources are limited, and the global oil, gas and coal production will be depleted in time to come, causing prices to escalate. Among all the available renewable sources, wind power systems have developed to prominent suppliers of electrical energy. Wind energy has seen an exponential increase, both in power ratings and overall capacity. The purpose of this project is to design and develop a switch magnetic field generator/motor for a vertical wind turbine using Neodymium Iron Boron magnets. Research was conducted on various designs of existing generator topologies and electromagnetism methods. The final design was selected based on complexity and cost. Throughout the semesters, a demo prototype has been re-designed to evaluate the effectiveness of the system. Using the theory of attraction and repulsion forces between the electromagnets, a rotational force is induce to create a driving motion for the prototype. The magnetic field strength of the electromagnets does not solely depend on the core material itself, but also on the amount of induced current and number of turns of coiled wire around the magnet. At the end of this project, I will evaluate my current prototype and give practical recommendations to improve the design. Harnessing free energy would be a continuous pursuit of the world and by going green in today’s context would greatly reduce the stress caused on nature.